ANALYSIS OF THE DEVELOPMENT TRENDS OF THE GLOBAL FINTECH MARKET - Vagner , Iryna; Kundrya-Vysotska , Oksana; Demko , Iryna (Socio-economic relations in the digital society, 2021)
Abstract. One of the promising ways of economic growth of enterprises is their innovative development. Thetwenty first century is marked not only by the development of science and technology but also by the emergenceand growth of the FinTech services market. The global financial crisis of 2008 triggered global changes in thefinancial services market, due to the spread of digital technologies, reduced confidence in the usual financialintermediaries in the post-crisis period, and changes in customer priorities for speed, availability, and ease ofobtaining financial services. Therefore, modern conditions determine the relevance of the study of the financialservices market, taking into account the emergence of FinTech innovations.The aim of the study is to generalize the theoretical foundations of the formation and development of recommendationsfor the impact of FinTech innovations on the development of domestic and foreign enterprises inthe context of globalization.The research was aimed at analyzing the history of development and key factors that influenced the formationof the FinTech market.The article uses the results of a large-scale survey of more than 22,000 Internet users in 20 countries, conductedin 2017 by Ernst & Young. According to this survey, it was found that more than 33 % of users are activeusers of Fintech services, which allowed us to analyze the stages of formation of the FinTech market to date.A study on the impact of the COVID-19 pandemic has been conducted regarding the growth of the FinTechmarket in the world and an analysis of the main trends in the development and promotion of the global fintechmarket in the first quarter of 2021.The main trends of FinTech market development in Ukraine and the world for the period 2021—2023 arehighlighted.Significant growth of investments in the FinTech market and globalization of processes in the industry: mergers,integration into the ecosystem, and assimilation of know-how into traditional banking allow us to concludethat the current generation of customers continues to avoid traditional financial institutions or abandon themin favor fully digital banks and embedded financial services. In response, traditional financial institutions aretrying to compete, increasing the pace of innovation and digitalization in various ways, which will continue in2021—2023. Given all these processes, the increase in the number of investments in the financial and technicalsector and the rapid growth of this segment is irreversible. in turn, needs further thorough research.Keywords: FinTech market, digital payments, investments, mega-rounds, Blockchain, D2C (direct to client),Insurtech acceleration, Regtech.JEL Classification G17, O32, O33Formulas: 0, fig.: 1; tabl.: 3; bibl.: 19.
Keywords: FinTech market; digital payments; investments; mega-rounds; Blockchain; 2C (direct to client), Insurtech acceleration; Regtech